Hatchability of the Eggs Aedesspp in Clean and Polluted Water - Fahri, Sukmal; Ariyani, Susy; Yamistada, Gustomo; Manulang, Eka S. (KnE Life Sciences, 2019)
Aedesspp is a type of mosquito that can carry dengue virus and causes dengue fever. Aedesspp can live in freshwater, polluted water, and household waste; oil pollution changes the behavior of mosquitoes breeding in polluted water, This study aims to determine the hatchability of Aedesspp eggs in oil-contaminated water media. The research experiment was carried out through post-test design, and the presentation of data was done by using a table. Data were processed by a t-test with a significance of α <0.05. Rainwater is the most preferred medium for hatching eggs of Aedesspp with an average of 3-4 head/day by the time they need to hatch < 6 days, while the hatchability of eggs of Aedesspp in regional water company media is better for hatching the eggs of Aedesspp than domestic wastewater, with an average of 2-3 head/day by the time they need to hatch < 9 days, the hatchability of eggs of Aedesspp on household wastewater with average 0-1 head/day by the time they need to hatch <14 days. In the oil contamination of water hatchability of eggs between 10-13 days. The change caused a mosquito egg hatchability change bionomics result of not finding media in the environment sample.